2019
DOI: 10.1002/ecm.1344
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of autocorrelation and bias in home range estimation

Abstract: Home range estimation is routine practice in ecological research. While advances in animal tracking technology have increased our capacity to collect data to support home range analysis, these same advances have also resulted in increasingly autocorrelated data. Consequently, the question of which home range estimator to use on modern, highly autocorrelated tracking data remains open. This question is particularly relevant given that most estimators assume independently sampled data. Here, we provide a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
236
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(242 citation statements)
references
References 91 publications
(381 reference statements)
5
236
0
1
Order By: Relevance
“…Individual home‐range sizes were estimated using autocorrelated kernel density estimation (AKDE) in the ctmm R package (Fleming & Calabrese, 2017b) for 95%, 75%, and 50% levels. The AKDE method was chosen as it corrects for temporal autocorrelation bias and is more accurate than the conventional kernel density estimation (KDE) with frequent fixes (here 10 min interval; Fleming and Calabrese, 2017a, 2017b, Noonan et al., ). Therefore, continuous time movement models (ctmm) were used to separate the continuous‐time movement process of an individual from the discrete‐time sampling process (Fleming et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual home‐range sizes were estimated using autocorrelated kernel density estimation (AKDE) in the ctmm R package (Fleming & Calabrese, 2017b) for 95%, 75%, and 50% levels. The AKDE method was chosen as it corrects for temporal autocorrelation bias and is more accurate than the conventional kernel density estimation (KDE) with frequent fixes (here 10 min interval; Fleming and Calabrese, 2017a, 2017b, Noonan et al., ). Therefore, continuous time movement models (ctmm) were used to separate the continuous‐time movement process of an individual from the discrete‐time sampling process (Fleming et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…with frequent fixes (here 10 min interval;Fleming and Calabrese, 2017a, 2017b, Noonan et al, 2019. Therefore, continuous time TA B L E 1 Ecological classification of the nine study species.…”
mentioning
confidence: 99%
“…Modeling has a number of attractive features common to analyses of animal movement data, including the incorporating of irregular sampling intervals and complex autocorrelation structures (Fleming et al, 2014a(Fleming et al, , 2014b, both of which have been shown to severely bias results if not handled properly (Noonan et al, 2018). Importantly, CTMM results are also displayed with appropriate confidence intervals, providing an important measure of the precision of parameter estimates.…”
Section: Continuous-time Movementmentioning
confidence: 99%
“…We chose to use AKDEs as opposed to conventional kernel density estimation (KDE), which explicitly assumes that location data are independent and identically distributed and often results in KDEs that underestimate activity space areas (Fleming & Calabrese, 2017;Fleming et al, 2015;Noonan et al, 2019). AKDE estimates the correlation structure in the data by fitting continuous-time movement models and selecting the best fitting model based on the approximate small sample size corrected Akaike information criterion to address the stronger autocorrelation that is associated with the ever-finer sampling of movement paths (Kays, Crofoot, Jetz, & Wikelski, 2015;Noonan et al, 2019). The number of days detected and the number of COAs were highly TA B L E 1 Summary of bloater tagged and released into eastern Lake Ontario over four periods in autumn 2016, spring 2017, autumn 2017, and autumn 2018 Mean ± SD (range) are shown for mass (g) and fork length (mm) and refers to tagged individuals.…”
Section: Horizontal Space Usementioning
confidence: 99%